2020
DOI: 10.1161/jaha.119.016334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epeleuton, a Novel Synthetic Second‐Generation n‐3 Fatty Acid, on Non‐Alcoholic Fatty Liver Disease, Triglycerides, Glycemic Control, and Cardiometabolic and Inflammatory Markers

Abstract: Background Epeleuton is 15‐hydroxy eicosapentaenoic acid ethyl ester, a second‐generation synthetic n‐3 fatty acid derivative of eicosapentaenoic acid. The primary objective was to assess the effect of epeleuton on markers of nonalcoholic fatty liver disease (NAFLD) with post hoc analyses of cardiometabolic markers. Methods and Results In a multicenter, randomized, double‐blind, placebo‐controlled trial, 96 adults with nonalcoholic fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In support of this finding, although administration of a second-generation synthetic EPA-ester — epeleuton — did not reduce liver stiffness and alanine aminotransferase activity in a phase IIa study in patients with non-alcoholic fatty liver disease, secondary analyses revealed intriguing metabolic effects. Specifically, the study investigators observed decreased levels of plasma triglycerides, vLDL and total cholesterol together with decreases in plasma glucose, HbA1c, insulin resistance and markers of endothelial activation 172 . These findings are further supported by experimental evidence that EPA-derived RvE1 decreases hyperinsulinaemia and hyperglycaemia in obese mice 173 .…”
Section: Specialized Pro-resolving Lipid Mediatorsmentioning
confidence: 90%
“…In support of this finding, although administration of a second-generation synthetic EPA-ester — epeleuton — did not reduce liver stiffness and alanine aminotransferase activity in a phase IIa study in patients with non-alcoholic fatty liver disease, secondary analyses revealed intriguing metabolic effects. Specifically, the study investigators observed decreased levels of plasma triglycerides, vLDL and total cholesterol together with decreases in plasma glucose, HbA1c, insulin resistance and markers of endothelial activation 172 . These findings are further supported by experimental evidence that EPA-derived RvE1 decreases hyperinsulinaemia and hyperglycaemia in obese mice 173 .…”
Section: Specialized Pro-resolving Lipid Mediatorsmentioning
confidence: 90%
“…Epeleuton is a synthetic n-3 fatty acid derivative of eicosapentaenoic acid that decreased triacylglycerols, improved glycaemic control and decreased markers of inflammation in a Phase II exploratory study (16 weeks) in individuals with obesity and NAFLD [134]. Epeleuton at the highest dose significantly decreased hepatic fat from baseline, although not significantly, vs placebo but it did not meet the primary endpoints of decreased ALT concentrations or liver stiffness.…”
Section: Drugs That Modulate Lipid Metabolic Pathwaysmentioning
confidence: 99%
“…In a phase 2a clinical trial of epeleuton in patients with obesity and NAFLD, serum biomarker data provides several hints regarding systemic effects of epeleuton on the host lipidome which may impact SARS-CoV-2 replication. In this phase 2a clinical trial epeleuton significantly decreased concentrations of plasma free fatty acids 11 , an observation that may be partly explained by the known inhibition of fatty acid synthase (FAS) by polyunsaturated fatty acids 25 . FAS is a homodimeric multifunctional enzyme that catalyzes fatty acid synthesis, synthesising palmitate from acetyl-CoA and malonyl-CoA in the presence of NADPH 26 .…”
Section: Discussionmentioning
confidence: 85%
“…A recent review by Theken et al outlined the important roles that lipids play in the viral life cycle both through direct interactions with viruses and by modulating various aspects of host biology 12 . As such, the observed effects of epeleuton in the Syrian hamster model are likely to consist of both direct antiviral effects and protection conferred by epeleuton’s effects on host immune response, including its known anti-inflammatory effects 11 . Recent studies suggest several potential targets for fatty acid binding to SARS-CoV-2 and provide evidence that polyunsaturated fatty acids can exert direct antiviral effects independent of host factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation